ANALYSIS THE EMOTIONAL CHARACTERS IN RILEY'S BRAIN IN INSIDEOUT MOVIE - IKA TRISNANTASARI (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2018)
Every human in this life have their own emotional thinking in their brain that influences every step to make it decisions such as what will you do after this? what do you want to eat today? what did you do for your living? and the other decisions in our life. Related to the statement above, this research aims to analyze the emotional characters in Riley's brain at the movie entitle inside out. Riley is 11th years old young girl, the main character in this movie. Inside out is an animation movie that contained some important scientific, parental, and psychological knowledge in every human's being and in around our environment. The knowledge presented in this movie is unique, interesting, meaningful, fun and easy to understand. This is a family movie that every person in the family can learn how to manage their self's emotional and how to interact well with other people and how to solve and react to the inherent problem. Therefore this is interesting research that fulfills what every person's problem in their life.